Bimetallic Heteronuclear Complexes Bridged with Ferrichexathiocyanate-Synthesis, Characterization and Antibacterial Properties - Uddin, Mohammad Nasir; Chowdhury, D A; Akter, Jashmin (The Journal of Pure and Applied Chemistry Research, 2014)
A number of heterobinuclear thiocyanato-bridged complexes of cations, [M(NH2X)6]2+ and [M(en)3]2+ (where en= Ethylenediamine, X = H, Ph; M= Ni, Cu, Cd, Zn), with ferrichexathiocyanate have been prepared. The complexes have been characterized by FT-IR, 13C NMR and UV-vis spectroscopy, metal analysis, magnetic and conductance studies.Â  The composition complexes has been proposed on the basis of experimental and literature evidences. The antibacterial activity of the prepared complexes has also been investigated against the gram positive-Bacillus cereus and gram negative- Salmonella typhi and Escherichia coli pathogens.